An investigation of the effects on follicular-embryonal development and pregnancy outcomes of serum and follicular fluid ischemia-modified albumin in cases of unexplained infertility receiving in vitro fertilization treatment - A. Yaylalı; M. Bakacak; Z. Bakacak; F. Tolun (Clinical and Experimental Obstetrics & Gynecology)
Objective: To show the effect of the oxidative stress index (OSI) of serum and follicular fluid and ischemia-modified albumin (IMA) levels on embryonic development and pregnancy in cases of unexplained infertility applied with in-vitro fertilization (IVF). Materials and Methods: A total of 80 patients were treated with antagonist protocol in the first cycle of IVF for a diagnosis of unexplained infertility. We recorded demographic data, blood and follicular fluid levels of follicle stimulating hormone (FSH), luteinizing hormone (LH), estradiol (E2), anti-Müllerian hormone (AMH), OSI and IMA. Using ROC analysis for follicular fluid OSI and IMA, patients were grouped according to the cutoff values determined (11.15 and 0.509, respectively). Results: No correlation was detected between serum OSI and IMA values and the implantation rate. In the follicular fluid OSI ≤ 11.15 group (n = 32), beta HCG positivity was seen in 65.6% of patients and live births in 50%. In the IMA ≤ 0.509 group (n = 24), beta HCG positivity was seen in 66.6% and live births in 50%. With respect to follicular fluid OSI and IMA values, the difference in terms of both beta HCG positivity and live birth rates was statistically significant (p = 0.003, p = 0.007, and p = 0.044, p = 0.028, respectively). The BMI value was significantly high in the IMA > 0.509 group (p < 0.05). Conclusions: In cases of unexplained infertility with high BMI, increased IMA but not OSI in follicular fluid during IVF treatment could be related to decreased implantation and live birth rates. Follicular fluid IMA levels below the cutoff value may predict pregnancy success.